2015
DOI: 10.1186/s12879-015-0966-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microscopic Observation Drug Susceptibility (MODS) and the string test for rapid diagnosis of pulmonary tuberculosis in HIV/AIDS patients in Bolivia

Abstract: BackgroundTuberculosis (TB) is the most common opportunistic infection and the leading cause of death in HIV-positive people worldwide. Diagnosing TB is difficult, and is more challenging in resource-scarce settings where culture-based diagnostic methods rely on poorly sensitive smear microscopy by Ziehl-Neelsen stain (ZN).MethodsWe performed a cross-sectional study examining the diagnostic utility of Microscopic Observation Drug Susceptibility liquid culture (MODS) versus traditional Ziehl-Neelsen staining (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because the string could also absorb sputum that has been swallowed, it has been proposed as a technique for obtaining lower respiratory specimens for tuberculosis testing in children. Several studies in adults have found that string samples have a diagnostic yield that is roughly similar to induced sputum [ 13 15 ]. The handful of studies in children have reported that > 80% could swallow the capsule and complete the test [ 4 , 16 , 17 ]; though this rate may vary by the child’s age, with the youngest children least able to swallow the capsule [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the string could also absorb sputum that has been swallowed, it has been proposed as a technique for obtaining lower respiratory specimens for tuberculosis testing in children. Several studies in adults have found that string samples have a diagnostic yield that is roughly similar to induced sputum [ 13 15 ]. The handful of studies in children have reported that > 80% could swallow the capsule and complete the test [ 4 , 16 , 17 ]; though this rate may vary by the child’s age, with the youngest children least able to swallow the capsule [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO has approved MODS for drug susceptibility screening for multidrug-resistant TB 19. Nucleic acid amplification testsNAATs involve amplification of DNA and RNA segments, to identify the microorganism in a specimen.…”
mentioning
confidence: 99%